US Economic Policy during Crisis: A Study of the Great Recession and Covid-19 Pandemic - Jasmine Kusumawardani; Rama Adianto S (Fenery Library, 2022)
This paper aims to provide an overview on how the United States respond to two economic crises: The Great Recession, and the Covid-19 Pandemic Economic crisis. Although the two crises were caused by very different issues: the Great Recession was caused by the housing and financial crisis, while the 2020 economic crisis was caused by Covid-19 pandemic, they both dealt a huge blow to the economy. Both crises caused unemployment numbers to jump, while purchasing power steeply declined. Through a literature study, this article looks at the financial decisions made by the US government and the Federal Reserve throughout the crises. This paper draws parallels between the fiscal and monetary policies of the US during crisis and the Keynesian model of the economy, which has boosted the economy and helped the country recover.